Association of long-term aspirin use with kidney disease progression - Lu, Jun Ling; Shrestha, Prabin; Streja, Elani; Kalantar-Zadeh, Kamyar; Kovesdy, Csaba P. (Frontiers in Medicine, 2023)
Background: Chronic microinflammation contributes to the progression of chronic kidney disease (CKD). Aspirin (ASA) has been used to treat inflammation for centuries. The effects of long-term low-dose ASA on CKD progression is unclear.We examined the association of long-term use of newly initiated low-dose ASA (50-200mg/day) with all-cause mortality using Cox proportional hazard models; with cardiovascular/cerebrovascular (CV) mortality and with end stage kidney disease (ESKD) using Fine and Gray competing risk regression models; with progression of CKD defined as patients' eGFR slopes steeper than -5 ml/min/1.73m 2 /year using logistic regression models in a nationwide cohort of US Veterans with incident CKD. Among 831,963 patients, we identified 385,457 who either initiated ASA (N=21,228) within one year of CKD diagnosis or never received ASA (N=364,229). We used propensity score matching to account for differences in key characteristics, yielding 29,480 patients (14,740 in each group).Results: In the matched cohort, over a 4.9-year median follow-up period, 11,846 (40.2%) patients (6,017 vs. 5,829 ASA users vs. non-users) died with 25.8% CV deaths, and 934 (3.2%) patients (476 vs. 458) reached ESKD. ASA users had a higher risk of faster decline of kidney functions, i.e. steeper slopes (OR 1.30 [95%CI: 1.18, 1.44], p<0.01), but didn't have apparent benefits on mortality (HR 0.97 [95%CI: 0.94, 1.01], p=0.17), CV mortality (Sub-Hazard Ratio [